HISTOLOGICAL AND MOLECULAR STUDIES OF THE EFFECTS OF TRAMADOL ON BRAIN, LIVER SND KIDNEY OF ADULT RABBITS - .Abdullah, B .A (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was to examine the histological changes in liver and kidney in tramadol -induced rabbits . This study was conducted on 10 adult male rabbits. Rabbits. were divided evenly into two groups: control group, received 1 ml normal saline 0.9%  Treated group received 0.3 ml of tramadol subcutaneously for 30 days. Results:  The histological analysis of the liver showed that the thickening wall  with minimal fibrosis in the periportal  area infiltration of inflammatory cells in necrotic change of the hepatocytes massive vacuolation of the hepatocyte, kupffer cell were present intensity in the sinusoid. The histopathological examination of kidney revealed lymphocyte infiltration , congestion ,glomerulus and tubular damage.  The tubular was containing hypertrophied epithelial cell which block the lumen .Brain tissues in treated groups showed degeneration of pyramidal cells in the cortex , congestion of the blood vessels in the cortex and medulla. The cortex certain pyramidal cell with slight enlarged. The random amplified polymorphic DNA (RAPD) based on Polymerase Chain Reaction (PCR) with 5 primers were applied, used to estimate fingerprinting and Genetic Distance for 3organs . the results showed clear difference in the number of packets as well as in the genetic dimension compared to the control group. Conclusion: The histopathological and molecular  alterations of liver,  kidney and brain tissues threw lights on the possible risks of increased hepatic, renal and neurological damages evoked by repeated administration of tramadol for long periods.